Prognostic Indicators of Cardiovascular Risk in Renal Disease - Hildreth, Cara (Frontiers in Physiology, 2012)
Although the annual mortality rate for end-stage renal disease is decreasing, likely due to an increase in kidney transplantation rate, the survival probability for end-stage renal disease patients from day one of dialysis has not changed, and is still poor with a five-year survival rate of approximately 34%. This is contributed to by a high prevalence of cardiovascular disease, which is the leading cause of death in end-stage renal disease patients. In order to improve survival outcomes, patients at high risk of cardiovascular related mortality need to be identified. Heart rate variability, baroreceptor sensitivity and baroreceptor reflex effectiveness index can be used to assess heart rate control and pulse wave velocity can be used to assess arterial stiffness. Each of these parameters may also predict cardiovascular mortality. This paper will discuss how heart rate variability, baroreceptor sensitivity, baroreceptor reflex effectiveness index and pulse wave velocity are altered in renal disease and the utility of these indices as markers of cardiac risk in this patient population.